Surveying the community of practice (COP) on poverty reduction, livelihoods & jobs - Lenaerts, Bert (International Rice Research Institute, 2024)
This report presents the findings of a survey conducted within the community of practice (COP) focused on Poverty Reduction, Livelihoods, and Jobs. The survey revealed a strong willingness among participants to engage actively in the Platform's initiatives and a collective enthusiasm for advancing poverty alleviation and employment creation goals. However, it also identified a significant need for enhanced capacity building, with many respondents expressing a desire for additional training and resources to more effectively contribute to the Platform's success. The report highlights these dual themes: a robust commitment to the shared objectives and the critical necessity for further development of skills and knowledge to achieve those goals. These findings underscore the importance of investing in capacity-building efforts to maximize the impact of the COP's work in poverty reduction and job creation.